2023
DOI: 10.1186/s12875-023-02086-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic has disrupted the continuity of care for chronic patients: evidence from a cross-sectional retrospective study in a developing country

Abstract: Background Any disruption in continuity of care for patients with chronic conditions can lead to poor outcomes for the patients as well as great damage for the community and the health system. This study aims to determine the continuity of care for patients with chronic conditions such as hypertension and diabetes during COVID-19 pandemic. Methods Through a cross-sectional retrospective study, data registered in six health centers in Yazd, Iran wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This study showed a decline in the health condition in chronic patients due to the different measures implemented to avoid contagion by COVID-19, such as confinement and restrictions (Dehghani Tafti et al, 2023). In addition, there was saturation in access to medical care, delays in treatment, low patient compliance with medications, as well as reduced physical activity and unhealthy lifestyle habits (Karatas et al, 2021).…”
Section: Ta B L Ementioning
confidence: 86%
See 1 more Smart Citation
“…This study showed a decline in the health condition in chronic patients due to the different measures implemented to avoid contagion by COVID-19, such as confinement and restrictions (Dehghani Tafti et al, 2023). In addition, there was saturation in access to medical care, delays in treatment, low patient compliance with medications, as well as reduced physical activity and unhealthy lifestyle habits (Karatas et al, 2021).…”
Section: Ta B L Ementioning
confidence: 86%
“…In Spain, some studies carried out only in diabetic patients found no significant changes during the lockdown and post-lockdown (Oliver et al, 2023;Palanca et al, 2022). However, to date, there are few studies that have evaluated the follow-up over time of clinical parameters in chronic patients (Dehghani Tafti et al, 2023;Fikree et al, 2023), and none have jointly analysed the most common chronic diseases as well as the short-and medium-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…Elective procedures and routine care were often postponed or cancelled, adversely affecting those with chronic conditions or in need of regular medical interventions. Moreover, it unveiled the vulnerabilities of specific demographic groups, such as the elderly and individuals with pre-existing conditions, thereby spotlighting the existing disparities in healthcare access and outcomes (Dehghani Tafti et al, 2023;Organization, 2020).…”
Section: Immediate Challengesmentioning
confidence: 99%
“…There was a lack of maintenance of chronic illnesses like diabetes and chronic heart diseases because primary healthcare facilities were overburdened with COVID-19 patients, while chronic patients were fearful to visit their primary physician or to call 911 during an emergency, such as a heart attack or stroke. 2 Of course, there is also reasonable possibility that some of the COVID-19 deaths could be due to other causes and not COVID-19. 3 There are reports of increase of death rates in many countries during the COVID-19 pandemic as well as shortening of life expectancy at birth.…”
Section: Type Of Study and Data Collectionmentioning
confidence: 99%